ANALISIS MOTIVASI KERJA PEGAWAI PADA PROGRAM PASCASARJANA UNIVERSITAS TADULAKO - Firsani, Sari Sagita (Katalogis, 2015)
This study aims to describe the motivation Employee Work Motivation Analysis in Tadulako University. Theories used as the basis of analysis is the motivation theory of Maslow, comprising Aspects of physiological needs are, safety needs, social needs, esteem needs, and self-actualization. Method of research used was descriptive qualitative research methods and data collection techniques by observation, interview, and documentation. Selection technique of informants is purposively as five people. Results showed that the work motivation of employees in the Postgraduate Program Tadulako some still expressed is less good and others expressed well, this is reflected in five aspects were examined still were still not very good, that is, 1) aspects of basic physiological needs, 2) aspects of need for security, 3) aspect of social needs whereas, 4) aspects of the needs of awards, and the 5) the aspect actualization needs is good.